Pemberdayaan masyarakat melalui peningkatan kualitas produk perikanan dan pertanian Kabupaten Takalar - Muhammad Junaedy Rahman; Ishak Ishak (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Tomasaju village of North Galesong district inTakalar regency has promising potential in fishery andagricultural. However, this condition does not make thecommunity healthier and prosperous. The problems found thatthe community 1) lack of facilities in processing and utilizingfisheries potential, 2) lack of general knowledge in managingagricultural products, 3) lack of knowledge about businessmanagement, and 4) lack of skills in packaging design. Thismain purpose of this program is processing fish into variousproducts made of fishes (fish biscuits, nugget, and abon),exploring Moringa plant into other agricultural products withhigher economic value, teaching business management andpackaging design. Thus, by conducting this program, it isexpected that their quality of life and income will improve.The target groups in this program are fishermen/ farmers,groups of housewives, young women, youth groups, and smallindustries that live in the targetted location. The methods usedare training, mentoring, lectures, practices and demonstrations.This program also involves partner institutions such as,Regional Government of Wajo and community leaders inNorth Galesong district. The number of students involved inthis program is 50 students from varied disciplines. The resultsof this study showed that 1) the community able to producedvaried fish products such as nugget, abon made of fish, 2) fishbiscuits, 3) noodle made of Moringa, and 4) the communityestablished their business management system, as well as theirproduct packaging design. Thus, it is expected that theirquality of life in Tomasaju village increased including theirincome.